2013
DOI: 10.1038/eye.2013.99
|View full text |Cite
|
Sign up to set email alerts
|

Displacement of foveal area toward optic disc after macular hole surgery with internal limiting membrane peeling

Abstract: Purpose To determine whether there is a displacement of the fovea toward the optic disc after successful macular hole (MH) surgery with internal limiting membrane (ILM) peeling. Methods The medical records of 54 eyes of 53 patients that had undergone pars plana vitrectomy with ILM peeling and gas or air tamponade for an idiopathic MH were evaluated. Spectral-domain optical coherence tomography (OCT) had been performed before and 46 months after the surgery. The preoperative distances between the center of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
56
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 25 publications
11
56
1
2
Order By: Relevance
“…We reported that the parafoveal retinal thickness was asymmetrical, e.g., thicker nasal retina and thinner temporal one [12,13]. Kawano et al showed a displacement of the fovea toward the optic disc after PPV with ILM peeling [17]. This displacement was confirmed by other studies [18,19].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We reported that the parafoveal retinal thickness was asymmetrical, e.g., thicker nasal retina and thinner temporal one [12,13]. Kawano et al showed a displacement of the fovea toward the optic disc after PPV with ILM peeling [17]. This displacement was confirmed by other studies [18,19].…”
Section: Discussionmentioning
confidence: 78%
“…Kawano et al and others reported that there was a shortening of the disc-to-fovea distance after MH surgery [17][18][19]. Therefore, we examined whether this change was related to the shape of the fovea.…”
Section: Correlation Between the Foveal Slope And The Discmacula Distmentioning
confidence: 93%
“…[12][13][14] Alterations in the retinal microstructure and structural stability due to ILM peeling have been postulated as a reason for nasal displacement of retina after MH surgery with ILM peeling. [15][16][17][18] The changes in retinal microstructure found in our study may also be partially caused by an alteration in structural stability due to ILM peeling. The frequency of the notching of tissue as well as the amount of foveal tissue elongation were relatively greater in the nasal direction, suggesting these phenomena may have some association with nasal displacement of the retina, as was reported in previous studies.…”
Section: Discussionmentioning
confidence: 82%
“…These cases were presumably congenital and developmental anomalies. Foveal displacement may be associated with intraocular surgeries such as retinal detachment or macular hole surgeries [6][7][8] . In a study performed Kawano et al [8] after vitrectomy with ILM peeling for macular hole, fovea of the patients displaced toward the optic disc.…”
Section: Discussionmentioning
confidence: 99%
“…Foveal displacement may be associated with intraocular surgeries such as retinal detachment or macular hole surgeries [6][7][8] . In a study performed Kawano et al [8] after vitrectomy with ILM peeling for macular hole, fovea of the patients displaced toward the optic disc. Displacement of the macula was also reported in cases with epiretinal membrane and epiretinal membrane peeling surgeries [9,10] .…”
Section: Discussionmentioning
confidence: 99%